The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1136/bcr.12.2010.3673
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalaemic quadriparesis: an unusual manifestation of dengue fever

Abstract: Dengue is the most common and widespread arthropod borne arboviral infection in the world today. Recent observations indicate that the clinical profile of dengue fever is changing with neurological manifestations being reported more frequently. A patient with dengue fever presented to us with symptoms suggestive of acute flaccid paralysis, and on subsequent investigation he was diagnosed as a case of hypokalaemic quadriparesis. Clinicians in the endemic area should be aware of such association of acute pure mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…[56] In our series, dengue virus infection was an important cause for hypokalemic paralysis. Four of our patients had hypokalemic paralysis due to dengue infection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…[56] In our series, dengue virus infection was an important cause for hypokalemic paralysis. Four of our patients had hypokalemic paralysis due to dengue infection.…”
Section: Discussionmentioning
confidence: 93%
“…Viral infections, such as dengue virus and chikungunya virus, have also been reported to precipitate hypokalemic paralysis. [567] Patients with hypokalemic paralysis need a diligent search for the possible etiology and potassium replacement therapy. Majority of hypokalemic paralysis patients usually recover completely without any residual disability.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of hypokalemia in dengue is unclear, but there is a certain hypothesis that it can be due to a transcellular shift in response to insulin release or self-limiting transient tubular dysfunction leading to potassium excretion [ 18 ]. Further study is needed in this regard and needs to be published, as dengue is on a rising trend and neurological complications are reported frequently now [ 19 , 20 ]. Physicians in endemic areas need to open their minds to unusual presentations like hypokalemic paralysis, which could be life-threatening but easily treatable.…”
Section: Discussionmentioning
confidence: 99%
“…Acute neuromuscular weakness is thought to be due to myositis, Guillain-Barré syndrome, or hypokalemic paralysis during dengue. While numerous authors have reported hypokalemic paralysis associated with dengue, most studies are based on case reports [3][4][5][6]. We present an intriguing case of hypokalemic paralysis associated with dengue in a young, pregnant female who fully recovered within 48 hours of potassium supplementation.…”
Section: Introductionmentioning
confidence: 88%